Nucleoporin Nup155 is part of the p53 network in liver cancer - Holzer, Kerstin; Drucker, Elisabeth; Baßler, Jochen; Rössler, Stephanie; Breuhahn, Kai; Hurt, Ed; Schirmacher, Peter; Singer, Stephan (Nature Communications, 2019)
The nuclear pore complex (NPC) is known to regulate p53 signaling and this has mainly been linked to peripheral NPC subunits. Here the authors show that Nup155 from the NPC inner ring regulates the p53 pathway by controlling p21 translation while also being a target of p53-mediated repression.
Gesehen am 22.07.2019